2010
DOI: 10.2118/116711-pa
|View full text |Cite
|
Sign up to set email alerts
|

A New Solution To Restore Productivity of Gas Wells With Condensate and Water Blocks

Abstract: Summary During production from gas-condensate reservoirs, significant productivity loss occurs after the pressure near the production wells drops below the dewpoint of the hydrocarbon fluid. Many of these gas reservoirs also have some water accumulation near the wells. This adds significantly to the total liquid blocking. Experiments were conducted using both outcrop sandstone and reservoir cores to measure the effect of liquid blocking on gas relative permeability. A chemical tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“… Using chemical treatment to modify the rock surface wettability from liquid-wet to neutral-wet (6,14).  Limitation: still at research stage (15,16).…”
Section: Wettability Alterationmentioning
confidence: 99%
“… Using chemical treatment to modify the rock surface wettability from liquid-wet to neutral-wet (6,14).  Limitation: still at research stage (15,16).…”
Section: Wettability Alterationmentioning
confidence: 99%
“…Although many approaches have been adopted for performance evaluation in the various industry sectors such as software industry, manufacturing industry, and even the construction industry (Bang et al 2010;Benestad et al 2009; de Aquino, de Lemos Meira 2009;Fleming et al 2010;Issa et al 2009;Niu, Dartnall 2010;Ren 2009;Yang, Paradi 2009), there are limited suitable approaches for the development of a project level engineering productivity metric. The Project-Level Productivity (PLP) index was developed by Ellis and Lee (2006) for monitoring multidiscipline daily labor productivity.…”
Section: Historical Background and Development Of The Pepmmentioning
confidence: 99%
“…Barnum et al (1995) found a dramatic decline in the production rates and hence reduction in gas recovery for wells with a permeability-thickness product of less than 1,000 md-ft. Takeda et al (1997) claimed that gravity force and interfacial tension are important factors in determining the relative permeability, and hence the buildup of condensate, around the wellbore. Barnum et al (1995) reported that the higher the well capacity (well capacity is the kh product, where k is the rock permeability and h is the reservoir thickness, and is a measure of the reservoir quality), the less the impact of the condensate banking on the productivity of wells drilled in condensate reservoirs. Simulation and laboratory studies have indicated that condensate saturation around the wellbore may reach 70% (Marokane et al 2002).…”
Section: Introductionmentioning
confidence: 98%
“…These models showed that the liquid condensation and accumulation around the wellbore results in a reduction in gas permeability and in a significant decline in the production rates of wells (Hinchman and Barree 1985;Clark 1985;Barnum et al 1995;Ahmed et al 1998). Barnum et al (1995) found a dramatic decline in the production rates and hence reduction in gas recovery for wells with a permeability-thickness product of less than 1,000 md-ft. Takeda et al (1997) claimed that gravity force and interfacial tension are important factors in determining the relative permeability, and hence the buildup of condensate, around the wellbore. Barnum et al (1995) reported that the higher the well capacity (well capacity is the kh product, where k is the rock permeability and h is the reservoir thickness, and is a measure of the reservoir quality), the less the impact of the condensate banking on the productivity of wells drilled in condensate reservoirs.…”
Section: Introductionmentioning
confidence: 99%